Pemberdayaan Petani Melalui Kajian dan Perluasan Adopsi Teknologi Pestisida Nabati pada Tanaman Kakao Di Kabupaten Kolaka - Iskandar, Iskandar; Mariadi, Mariadi; Nikoyan, Anas (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
The aim of this research were is to farmers Cacao in this cases influence on depending and development technology of application Pestisida Nabati (TPN) in the overcome germ of cocoa. This research is done in Kolaka Regency, with estimated that location is the center of productivity of agribusiness commodity. This research ll’ does in Southeast Sulawesi and the method of research that uses questioner, in-depth interview, and observed in located. Data that gets in the field analysis Quantitative to describing the result of the analysis. The result of research showed that application of technology natural pesticide going to minimize or overcome infection the Germ of Cocoa, and ll’be able to in the breach for product and then all’be improving cocoa of Quality it. There are were showed at the experiment group, quality of grain cocoa with using vegetable pesticide is showed with extra rain. The average of hard cocoa can be to 100-120 grain/gram, and at the control group have to 117-160 grain/gram, this value is showed up of by C to B. It’s meaning application Pestisida Nabati to be able to overcome the germ of cocoa.